Meningkatkan Kapasitas Berpikir Kritis untuk Tantangan Era Disrupsi 4.0 Berdasarkan Inspirasi Sabda Rasulullah dengan Menggunakan Analisis Higher Order Thinking Skills - Wahyudin Darmalaksana; Eva Meidi Kulsum (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the inspiration of the hadith related to improving critical thinking skills. This study uses a qualitative approach by applying the takhrij and syarah hadith methods through the analysis of Higher Order Thinking Skills. The results of this study indicate that the hadith studied is maqbul ma'mul bih in the sense that it is accepted and can be used as a justification for practicing Islam. The discussion of this research explains that the studied hadith directs generations of students of knowledge to strengthen the spirit, mind, and body and are required to be able to analyze, evaluate, and create according to the parameters of Higher Order Thinking Skills. This study concludes that the hadith of the Prophet SAW. save valuable inspiration when excavations are carried out with relevant theories to strengthen critical thinking skills in responding to the challenges of the era of disruption of the industrial revolution 4.0.